Sepsis-3 and its Assesment Tools (Sofa and Qsofa): Historical Evolution, Clinical Utility and Criticisms - Bhagaskara, Pandya; Wiqoyah, Nurul (Universitas Mohammad Husni Thamrin, 2025)
Sepsis remains a major global health problem with high morbidity and mortality. Over the past three decades, evolving consensus definitions have sought to improve diagnostic accuracy and patient outcomes. The latest definition, Sepsis-3, defines sepsis as life-threatening organ dysfunction caused by a dysregulated host response to infection, with the Sequential Organ Failure Assessment (SOFA) and quick SOFA (qSOFA) as key tools. This review outlines the historical development of sepsis definitions, examines the role of SOFA and qSOFA, and summarizes their strengths and criticisms. Sepsis-3 marked a shift from inflammation-based to organ dysfunction–centered criteria. Evidence shows that SOFA is highly accurate for prognosis in intensive care, while qSOFA is useful for bedside risk stratification outside the ICU. Both outperform systemic inflammatory response syndrome (SIRS) in specificity, though SOFA requires laboratory parameters and qSOFA shows reduced sensitivity. Some authors argue SIRS should not be entirely discarded due to its early recognition value. In conclusion, Sepsis-3 advanced the standardization of sepsis definitions, yet challenges remain, and this article was written to provide a concise overview of its evolution, utility, and ongoing debates. Keywords: Sepsis-3, SOFA, qSOFA, SIRS, sepsis definitions